Slc26a3/Dra and Slc26a6 in Murine Ameloblasts. (December 2015) - Jalali, R.; Zandieh-Doulabi, B.; DenBesten, P.K.; Seidler, U.; Riederer, B.; Wedenoja, S.; Micha, D.; Bronckers, A.L.J.J.
Formation of apatite crystals during enamel development generates protons. To sustain mineral accretion, maturation ameloblasts need to buffer these protons. The presence of cytosolic carbonic anhydrases, the basolateral Na + bicarbonate cotransporter Nbce1, and the basolateral anion exchanger Ae2a, b in maturation ameloblasts suggests that these cells secrete bicarbonates into the forming enamel, but it is unknown by which mechanism. Solute carrier (Slc) family 26A encodes different anion exchangers that exchange Cl – /HCO3 –, including Slc26a3/Dra, Slc26a6/Pat-1, and Slc26a4/pendrin. Previously, we showed that pendrin is expressed in ameloblasts but is not critical for enamel formation. In this study, we tested the hypothesis that maturation ameloblasts express Dra and Slc26a6 to secrete bicarbonate into the enamel space in exchange for Cl – . Real-time polymerase chain reaction detected mRNA transcripts for Dra and Slc26a6 in mouse incisor enamel organs, and Western blotting confirmed their translation into protein. Both isoforms were immunolocalized in ameloblasts, principally at maturation stage. Mice with null mutation of either Dra or Slc26a6 had a normal dental or skeletal phenotype without changes in mineral density, as measured by micro–computed tomography. In enamel organs of Slc26a6- null mice, Dra and pendrin protein levels were both elevated by 52% and 55%, respectively. The amount of Slc26a6 protein was unchanged in enamel organs of Ae2a, b - and Cftr -null mice but reduced in Dra -null mice by 36%. Our data show that ameloblasts express Dra, pendrin, or Slc26a6 but each of these separately is not critical for formation of dental enamel. The data suggest that in ameloblasts, Slc26a isoforms can functionally compensate for one another.